Antibacterial mechanism of sucrose laurate against Bacillus cereus by attacking multiple targets and its application in milk beverage. (April 2022) - Ning, Yawei; Ma, Mengge; Zhang, Yajuan; Zhang, Dongchun; Hou, Linlin; Yang, Kun; Fu, Yunan; Wang, Zhixin; Jia, Yingmin
Graphical abstract: Highlights: SL is a promising dual-functional additive (emulsification, antibacterial activity). Antibacterial mechanism was elucidated at the cellular and molecular levels. Action mode was revealed from the aspect of metabolic pathways by proteomic analysis. SL was evidenced to show promising applicational effect in milk beverage. This investigation could provide scientific basis for the application of SL. Abstract: Sucrose laurate (SL) is a promising dual-functional additive due to its emulsification and antibacterial activity. However, the knowledge on the antibacterial action of SL against Bacillus cereus was lacking, and thus it was investigated from multiple targets. The antibacterial results demonstrated that the minimum inhibitory concentration of SL was 0.3125 mg/mL, and the time-killing curve confirmed the strong antibacterial activity of SL. The alkaline phosphatase assay suggested that SL disrupted the cell wall integrity. The flow cytometry and fluorescence spectroscopy analysis indicated that SL damaged the integrity of cell membrane and dissipated the transmembrane potential, resulting in the leakage of intracellular materials, which were further supported by scanning electron microscopy and transmission electron microscopy. iTRAQ-based proteomic analysis indicated that SL down-regulated cell wall-associated hydrolase, inhibited the synthesis of fatty acids, influenced nucleic acid synthesis, disturbed amino acid metabolism, and blocked HMP pathway and TCA cycle. Finally, the promising application of SL was evidenced in milk beverage. This investigation could provide scientific basis for the practical application of SL as a dual-functional food additive.